Law on fisheries - The National Assembly (2003)
This Law shall apply to fishery activities of Vietnamese organizations and individuals and foreign organizations and individuals on the land, islands, in the internal waters, the territorial sea, the exclusive economic zone and continental shelf of the Socialist Republic of Vietnam